1. Trends in Indian Theology 2. Christophany: The Fullness of Man 3. Faith and Order: Towards a North American Conference (Study Guide) 4. itualistic Culture of Sri Jagannatha: As Revealed in Niladrimahodaya - Vineeth, V F; Athappilly, Sebastian; Edattukaran, Wilson; Alackapally, Sebastian (Journal of Dharma, 2005)
1. Kuncheria Pathil, Trends in Indian Theology, Bangalore: ATC Publications, 2005, pages 177, ISBN: 81-7086-364-3. 2. Raimon Panikkar, Christophany: The Fullness of Man, trans. Alfred DiLascia, Faith Meets Faith Series, Maryknoll: Orbis Books, 2004, pages xxi + 214, ISBN: 1-57075-564-7. 3. Norman A. Hjelm ed., Faith and Order: Towards a North American Conference (Study Guide), Michigan: William B. Eerdmans Publishing Company, 2005, pages x+50, ISBN: 0-8028-2914-7. 4. Basudev Mishra, Ritualistic Culture of Sri Jagannatha: As Revealed in Niladrimahodaya, , Puri: Utkal Sanskrit Research Society, 2005, pages viii+140.